Development of a one-step centrifugal extraction method for simultaneous determination of multiple types of pesticides and their metabolites in urine, serum, and breast milk - Zhang, Chi; Zhan, Zhipeng; Li, Jingguang; Wu, Yongning; Chen, Dawei; Li, Hong (Journal of Chromatography A, 2025)
•A one-step centrifugal-assisted CIPS method was developed in biological samples.•Centrifugal-assisted technique enhances performance in sample preparation.•Multiplexed tSIM method was used for highly sensitive and accurate quantification.•The greenness profile and practicality of this method were assessed. An efficient and highly sensitive analytical method was developed for the simultaneous determination of neonicotinoids, benzopyrazoles, diamide insecticides and chlorothalonil fungicide and their metabolites in biological samples (urine, serum and breast milk). The method combines centrifugal-assisted cold-induced phase separation (CIPS) with liquid chromatography and high-resolution mass spectrometry (LCHRMS) in multiplexed-targeted single-ion monitoring (MSX-tSIM) mode to ensure high sensitivity and accuracy. Sample preparation parameters such as solvent selection and acetonitrile/water ratio were optimized to improve analyte recovery and minimize matrix effects. The method exhibited excellent accuracy, precision, and low limit of quantification (LLOQ) in the range of 0.01–0.2 µg/L, with recoveries ranging from 72.6 % to 109.6 % in a variety of biological matrices. The method showed good linearity (R² > 0.993) and was suitable for the detection of trace pesticide levels in complex biological samples. Biomonitoring of pooled samples revealed widespread neonicotinoids contamination, with fipronil metabolites detected only in serum and breast milk, raising concerns about the potential accumulation of pesticide metabolites in the human body, especially in susceptible populations. This method provides a cost-effective and environmentally friendly alternative to traditional methods, facilitates large-scale human biomonitoring studies, and supports pesticide exposure risk assessment.